Long-term results of manual therapy of early manifestations of perfusion insufficiency vertebral-basilar system in children - Ye. A. Shumakov; G. I. Shumakher; A. S. Malikov; A. A. Olejnikov; V. V. Bondarev; M. P. Kuznetsova (Бюллетень сибирской медицины)
Article is devoted to studying of the long-term results of manual therapy of early manifestations of perfusion insufficiency (EMPI) vertebral-basilar system (VBS) in children. At clinical inspection of 97 patients in 3 years after treatment relapse EM of VBI has been revealed at 28 patients (28.9%). The principal causes of relapse EM of VBS were relapses of rotational dislocation С1 and muscle spasms of a neck in a combination to relapse of the carriage disorders and hypermobility in cervical department of a backbone.